Numerical Simulations of a Two-dimensional Vertically Averaged Air Pollution Measurement in a Street Canyon - Hasakarn Thongzunhor; Nopparat Pochai (My University, 2022)
Air pollution is the release of pollutants into the atmosphere that are harmful to human health and the ecosystem as a whole.Initially, urban air pollution was considered to be a regional problem caused largely by domestic heating and industrial emissions, both of which are now well under control.The building's canyon structure and the geometry of the streets in urban areas are street canyons.Side Street connects the two sides of the street, which are made up of portions of buildings.Street canyons, which are urban streets bordered on both sides by structures, have shown high levels of pollution.Pedestrians, cyclists, vehicles, and residents will most likely be surrounded by pollution concentrations higher than current air quality limits on these walkways.The research is focused on detecting air pollution in a street canyon.There will be an introduction to a transient two-dimensional advection-diffusion equation.A two-dimensional vertically averaged air pollution measurement model is utilized to characterize the air pollution concentration along a street canyon.The model delivers the pollutant concentration in the air each and every time.The model's air pollutant concentration is approximated using a finite difference technique.An approximation approach to open and closed boundary conditions is proposed.Wind direction effects are also modelled.The suggested numerical approaches performed well in producing a high level of agreement.Simple explicit schemes have the benefit of being simple to compute.These techniques may be used to simulate air pollution measurements in a variety of street canyons.
Keywords: Street Canyon; Air Quality Monitoring and Forecasting